2014
DOI: 10.1097/cad.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Integrins

Abstract: Integrins are a large family of cell surface receptors that bind extracellular matrix proteins. The interaction of integrins with extracellular matrix activates a number of intracellular signaling pathways involved in cell proliferation, differentiation, motility, and other essential cell functions. Integrins are critically important to both health and disease. In this review, we first describe the structure, functions, and signaling characteristics of integrins. We then discuss the roles of integrins in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 174 publications
(212 reference statements)
0
7
0
Order By: Relevance
“…The functional role of integrins in tumourigenesis entails more than that of a mechanistic receptor for cell-cell and cell-matrix attachment 36 . Integrin stimulation activates a number of intracellular signalling pathways involved in cell proliferation, differentiation, motility and other essential cell functions 37 and may not always directly correlate with malignant behaviour. Zutter et al .…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of integrins in tumourigenesis entails more than that of a mechanistic receptor for cell-cell and cell-matrix attachment 36 . Integrin stimulation activates a number of intracellular signalling pathways involved in cell proliferation, differentiation, motility and other essential cell functions 37 and may not always directly correlate with malignant behaviour. Zutter et al .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of integrins with the extracellular matrix activates a number of intracellular signaling pathways involved in cell proliferation, differentiation, motility, and other essential cell functions. 100 It has been shown that glioblastoma and its associated vasculature widely express integrins. 3 Preclinical studies have demonstrated that integrin inhibition induces apoptosis of human glioma cells and that integrin inhibitors prolong survival of immunodeficient mice carrying glioma xenografts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified a linkage between an altered integrin expression, tumor cell progression, metastasis, and chemoresistance [1,5,57]. …”
Section: Discussionmentioning
confidence: 99%